Little Miss Neat - Hargreaves, Roger (World international Limited, 1981)
Little Miss Neat is the 3rd book in the Little Miss series. Little Miss Neat is as neat as two pins, and lives in Two pin Cottage. When she goes on holiday, Mr. Muddle comes to visit her empty house.
Keywords: Juvenile Fiction-Book